GROUND ICING OF AIRCRAFT: MEASURES TO PREVENT ACCIDENTS - M. V. Storozhuk (Научный вестник МГТУ ГА, 2016)
This article discusses the pre-conditions for aircraft ground icing, the dynamics of traffic increase in the Russian avia-tion, the urgency of the problem and the ways and methods of it is solution and improvement of aircraft anti-icing protec-tion.